Entrepreneurial Orientation and Competitiveness of Telecommunication Firms in Rivers State, Nigeria - Macaulay Enyindah Wegwu; Sunny Joshua Princewill (Newinera Publisher, 2022)
This research investigated the connection between the entrepreneurial mindset of telecommunications companies in Rivers State, Nigeria, and their level of market competitiveness. In the state of Rivers, there were a total of 139 managers working for four different telecommunications companies: MTN, 9Mobile, Airtel, and Globacom. The researchers used a straightforward random selection method to choose 103 participants for their investigation. The delivery of a structured questionnaire was used to obtain the primary data for this study. Using Spearman's Rank Order Correlation Coefficient and the Statistical Package for the Social Sciences (SPSS) version 22.0, we examined whether or not the provided hypotheses were supported by the data. According to the findings of the research, the two aspects of entrepreneurial orientation that were chosen (innovativeness and proactiveness) have a substantial connection to an organization's level of competitiveness (quality and market share). According to the findings of the study, the management of telecommunications companies should have an innovative plan to fund innovative ideas, experimentation, and creative processes; they should also introduce new products and services; and they should invest significantly in research and development. Additionally, the management of companies that deal in telecommunications have to take the initiative in the launch of new goods and services whenever possible. When it comes to the current state of the telecommunications industry, they should be recognized as a reputable brand. They should also react more quickly than their rivals do to educational and research opportunities.